India telemedicine's great new frontier. - Harris, G.
Champions of telemedicine, the systematic application of information and telecommunications technology to the practice of healthcare, have been very patient. By the 1980s, pilot projects begun amid great hopes in the 1950s and 1960s had fizzled out for the most part. More recently, however, telemedicine has undergone something of a resurgence, as technology has begun catching up with aspirations. Perhaps nowhere is this renaissance so vitally needed as in India. With their dependence on high-bandwidth real-time technologies, most telemedicine projects of the past decade have been ill suited to India. Now, though, new hopes are being engendered there by the confluence of low-bandwidth telemedicine with a growing middle class, an improving telecommunications infrastructure, a world-class software industry, and a medical community open to new ideas
Keywords: India; Low-bandwidth telemedicine; Medical community; Real-time technologies; Software industry; Telecommunications infrastructure